Digitalization, Finance, and Governance for Blue Inclusive Growth in Sulampua - Andini Kusumawardhani; Moh. Najikhul Fajri; Backtiar Putra Pratama (Kirana Publisher (KNPub), 2026)
This study aims to analyze the spillover effects of digitalization, financing, and institutional governance on inclusive blue economic growth in SULAMPUA. By applying aggregated crosstabulation (PODES) to a panel data model of 144 regencies/cities during 2019–2022 in the Sulawesi, Maluku, and Papua regions. This study employs three analytical techniques, namely cluster analysis: k-means and location quotient to determine blue economic centers; efficiency analysis: Luenberger productivity index to determine inclusive blue growth; and static panel regression to determine digitalization, financing, and governance. The results show that digitalization and banking financing have a significant positive effect on inclusive blue growth.